Sífilis secundaria en cavidad oral: Reporte de dos casos Oral secondary syphilis: Two cases report - M G Díaz; E Carbó; M V Guardati; M A Reyes; J Weidmann; M Eletti; J L Iribas (Asociación Argentina de Dermatología, 2008)
La sífilis es una enfermedad infecciosa humana causada por una bacteria: el Treponema pallidum. La enfermedad es transmitida por contacto directo a través de lesiones durante el estadio primario y secundario, por vía transplacentaria intrauterina o a través del canal uterino; puede afectar cualquier órgano de la economía causando un número infinito de presentaciones clínicas. La sífilis secundaria cursa con manifestaciones mucocutáneas características y eventual sintomatología general. La presentación clínica de nuestros dos pacientes es singular ya que solo poseían lesiones en la cavidad oral. La respuesta al tratamiento instaurado fue buena. Syphilis is a human infectious disease caused by the bacterium Treponema pallidum. The disease is transmitted by direct contact with a lesion during the primary or secondary stages, in utero by the transplacental route, or during delivery as the baby passes through an infected canal. The bacterium may infect any organ, causing an infinite number of clinical presentations. Secondary syphilis is characterized by mucocutaneous lesions, a flulike syndrome, and generalized adenopathy. Hepatosplenomegaly may be present. The oral mucosa is the second most frequent site of luetic lesions; the genital areas are the most frequent. In the oral cavity, the most characteristic lesion is a whitish mucosal patch, normally located on the lips, tongue, or palate, which is extremely contagious. The differential diagnosis of this lesion may include oral squamous carcinoma, leukoplakia, candidosis, lichen planus, and hairy oral leukoplakia. Definitive diagnosis is based on clinical information and completed by laboratory examinations even the biopsy can help us. With the diagnosis of secondary syphilis treatment with penicillin G benzathine must be started. We present two cases of secondary syphilis with oral lesions only; the first one, a man with macule covered with a whitish membrane on palate mucosa and a lateral neck adenopathy. The lesion had been present for three months. The second one, a woman with painful whitish mucosal patch since two weeks ago. No fever or flulike syndrome. Luetic serologic tests were positive in both cases and in the first one the biopsy showed a chronic inflammatory infiltrate. The drug of choice in the treatment of our patients was benzathine penicillin G.